The future of environmental ethics - Rolston, Holmes, 1932-2025, author; Utah Valley University, publisher (Colorado State University. Libraries, 2007)
The environment is on the world agenda, also on the ethical frontier, for the foreseeable future. Environmental ethics is about saving things past, still present. Environmental ethics is equally about future nature, without analogy in our past. Living at one of the ruptures of history, modern cultures threaten the stability, beauty, and integrity of Earth, and thereby of the cultures superposed on Earth. Environmental ethics must find a satisfactory fit for humans in the larger communities of life on Earth.
Keywords: sustainable development; life on Earth; environmental justice; environmental ethics; millennium ecosystem assessment; global development; environmental values; environmental alarms; biological controls; consumption